Pendidikan Karakter Di Era Society 5.0 Melalui Progam Tahfidz Al-Qur’an Di Mi Terpadu Tahfizhul Qur’an Al-Ma’shum Surakarta - Hanik, Elya Umi; Baiturohmah, Risma (ILUMINASI: Journal of Research in Education, 2024)
Character education is the role of educational institutions to give birth to generations who have good behavior and are in accordance with the norms that apply in society. The growing development of this technology is an interesting thing to discuss and pay attention to, because issues regarding this character have become very important issues lately. Therefore, cultivating and strengthening self-character is very important because it forms and strengthens self-identity or identity so that children can behave well. Character is a characteristic of behavior in everyday life that is in a person who is characteristic. Character is currently a problem that really needs attention. Because along with the development of the times, namely the emergence of Society 5.0, this makes it easier for humans in this life, it also gives bad things to life. Society 5.0 is defined as a technology-based human-centered citizen. In dealing with today's character problems at the Integrated MI Tahfizhul Qur'al Al-Ma'shum (MITTQUM) school, it provides a superior and mandatory program, namely the tahfidz program. Strengthening student character education through the Al-Qur'an tahfidz program not only improves the quality of reading and memorization, but also the emergence of character values contained in the Al-Qur'an in students. The program is implemented so that children have good characteristics, such as religious character, discipline and responsibility. This character is formed because of the activities carried out, such as muroja'ah, depositing memorization, targeting memorization at each grade level, and other religious activities such as dhuha prayers and congregational prayers in congregation.